Evaluation of Essential Care Skills for Nurses Working at the Selected Infertility Clinics in Tehran, Iran, within 2016-2017: Nurses' Perspectives - Fahime Hasanbeigi; Mitra Zandi; Anoshirvan Kazamnejad; Atefe Salimi Akin Abadi (Mashhad University of Medical Sciences, 2020)
Advancements in assisted reproductive technology (ART) has increased the nurses' contribution to the provision of ART services. The present descriptive cross-sectional study aimed to determine essential care skills for nurses working at the selected infertility clinics in Tehran, Iran, based on their perspectives within 2016-2017. A total of 59 nurses were selected via a convenience sampling method and the data were collected using a researcher-made questionnaire. Data analysis was performed using SPSS software (version 21). Furthermore, the results of the Spearman's rank correlation coefficient highlighted items associated with three domains of knowledge, attitudes, and practices required for nurses from their perspectives (94.9%). Given that nurses have constant contact with clients in infertility clinics and considering the lack of studies on essential care skills for nurses working at such centers, the results of this study would help to define job descriptions and determine the necessary care skills for the nurses.